Web-based Course Management System - Zgouzi, Ayada Ibrahim M (2012)
The importance of the web-based applications is notable during the last decades especially in educational institutions. This project focuses on an existing problem being faced by the members of the school of Computing (SOC) at the Universiti Utara Malaysia (UUM). In addition, it also addresses on the difficulty of obtaining information which relates lecturers, their current registered courses, and their past semesters history. Whereby this information can only be viewed by the university members according to their authorities and needs. Hence, the clerk can efficiently make a decision on specific course which needs to be allocated to a lecturer by listing the current and past teaching history of them. Clerk can register, update courses, lecturers information, and allocate courses to lecturers. Clerk also can register, update, and search ISO documents. Program coordinator can allocate the proper course coordinator and moderator to courses. Moreover, the WBCMS has search tools where users (Clerk, Program Coordinator, Lecturers, and Students) can search by course, lecturer, session, or semester.